Spatial-Temporal Analysis of Land Cover Change and Oil Palm Expansion in Gunung Mas - Andini, Putri; Nurlika, Rahayu; Salma, Yuriduna; Wicaksono, Arditya (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Abstract: The area of oil palm plantations in Indonesia has increased over time. The growth of oil palm plantations even exceeds the percentage of the area of paddy fields, especially in Gunung Mas Regency. This phenomenon is accompanied by the implementation of "Regional Regulation No. 1 of 2020 concerning Land Fire Control". The regulation aims to prevent land fires due to human activities. However, local people believe that burning can increase land productivity. As a result, many people convert their land to plant oil palm, because it is considered to guarantee economic improvement compared to paddy fields. Remote sensing satellite imagery is the basis and main source in the analysis. With spatio-temporal analysis, mapping of land use changes in a certain period of time and its relationship with the distribution of agricultural wet and dry areas. As a result, the proportion of palm oil land in Gunung Mas Regency is higher than the proportion of paddy fields. If oil palm expansion continues in the future, agricultural drought could become more widespread. Keywords: Expansion of oil palm, Land use change, Paddy Fields, Remote sensing, Spatio-Temporal Analysis